At the Intersection of Authority and Threat: A Philological Analysis of Mataram Letter in Southern Cirebon (1687) - Tendi, Tendi (PT. Student Rihlah Indonesia, 2025)
This study examines the dynamics of power and official directives through a philological approach, focusing on letter issued by the Mataram Sultanate to the southern Cirebon region in 1687. By employing a philological perspective, the research investigates not only the textual content but also the material, linguistic, and contextual aspects of the manuscripts. The findings demonstrate that Mataram letter functioned not solely as administrative instruments but also as tools of internal diplomacy and social control, enforcing laws, issuing commands, and signaling warnings to local rulers. Philological examination uncovers layered meanings within the texts, highlighting how language, manuscript form, and historical context collectively shaped the messages sent by the Sultanate to southern Cirebon at the close of the seventeenth century. Ultimately, this study provides a multidimensional understanding of official Mataram documents: as instruments of administration, mechanisms of political legitimacy, and vehicles of social influence. It offers novel insights for Javanese history, colonial administrative studies, and Nusantara textual philology.